Healing the Heart with Nature: An Ecotherapeutic Study of Matthiessen's The Snow Leopard - Upadhyay, Toya Nath (SCHOLARS: Journal of Arts & Humanities, 2020)
This study explores the man and nature relationship in Peter Matthiessen's travel book, The Snow Leopard (1977), from the ecotherapeutic perspective. It demonstrates how Matthiessen's heart, bereft by the unexpected and untimely demise of his wife, receives healing from his interaction with the pristine nature at the Crystal Mountain of Nepal. The study also illustrates how this psychologically tormented Matthiessen from the West, in turn, extends his deep reverence to the beauty of the industrially less affected regions of the non-West as well as to the animals and indigenous spiritual practices existing there. For the analytic purpose, the study brings various critics' responses to the book into discussion as well as borrows key theoretical ideas from various ecotherapists such as Linda Buzzell, Craig Chalquist, Howard Clinebell and others.